Teacher–Child Interaction Quality Buffers Negative Associations Between Challenging Behaviors in Preschool Classroom Contexts and Language and Literacy Skills. (November 2020) - Bulotsky Shearer, Rebecca J.; Bichay-Awadalla, Krystal; Bailey, Jhonelle; Futterer, Jenna; Qi, Cathy Huaqing
Guided by an ecological model, we tested whether teacher–child interaction quality buffered the negative associations between challenging behavior within preschool classroom contexts and language and literacy skills. Associations were examined for a sample of children enrolled an urban Head Start program ( N = 304 children across 53 classrooms). Findings from multilevel models supported direct associations between challenging behaviors within preschool learning contexts and language outcomes. Higher instructional support was associated with higher language and literacy outcomes for all children within classrooms regardless of behavioral risk. Higher classroom organization was directly associated with higher classroom literacy skills. Emotional support moderated associations between challenging behaviors in teacher contexts and literacy outcomes. Implications for future research, policy, and practice are discussed.